Economic analysis of the effectiveness of complex rehabilitation in children with spastic forms of cerebral palsy with injections of botulinum neurotoxin type A and without it - V. A. Zmanovskaya; D. A. Popkov; A. L. Kurenkov; A. I. Uzdina; E. V. Levitina (Izdatelstvo OKI, 2018)
Purpose. Comparative economic analysis of complex rehabilitation of children with cerebral palsy (CP) with and without injections of botulinum neurotoxin type A (Dysport®, BoNT-A). Materials and methods. We clinically followed up 149 children with spastic forms of cerebral palsy (GMFCS II-IV) - 78 boys and 71 girls in the age period from 2 to 14 years (108 children who received intramuscular BoNT-A injections and 41 children who underwent similar complex treatment without it). In the budget impact analysis (BIA) only direct medical costs were taken: the cost of pharmacotherapy BoNT-A, rehabilitation care and surgery. Results. Children with CP of the main group needed surgical correction for the first time by 10.5±2.8 years, 4.6 % (5 children) of them needed repeated 95 % (39 children) of the comparison group during the period of active growth from 10 to 12 years. As a result, the BIA found that the use of the treatment scheme for children with CP using abobotulinumtoxinA will save the budget of 24 744 690 RUB per 100 children compared to standard therapy for 12 years of observation. During the CEA it was found that to achieve 1 % efficiency in children with CP with the use of abobotulinumtoxin A requires 1 854 426 RUB, and to achieve a similar result without BoNT-A - 40 702 271 RUB. Including abobotulinumtoxinA injections in the comprehensive rehabilitation of children with CP would allow to treat additional 14 % children (compared to a treatment without BoNT-A ) with the same budget. Conclusion. It was found that the use of treatment regimens for children with cerebral palsy using the BoNT-A is economically justified. Long-term therapy of children with CP with Dysport® during a 12-year-follow-up has considerably improved clinical outcomes and could provide a saving of 24 744 690 rubles compared with a standard therapy per 100 patients. Considering the register of children with CP in the Tyumen region on 01 January, 2018, the budget savings could account for 5,938,726 rubles a year.